Analysis of the affirmed with the addition of acrylamide polymer and cement, Ocobamba, Chincheros, Apurimac 2023 - Gomez-Villa, Isael (2023)
For a long time, unpaved roads have been built in road networks with little trafficability for vehicles where the upper folder of this is the affirmed layer, this material is of a granular type that is exposed to external agents that directly weaken the layer resistance. The objective is to determine the layer behavior of the affirmed with the addition of acrylamide polymer and cement, Ocobamba, Chincheros, Apurímac 2023. The methodology is of the applied type, experimental design, quantitative approach, the population and sample that is evaluated is the Chalhuany quarry of 625 m2 that will be used for stabilization with acrylamide polymer chemical additive and cement. In the 100% CBR test with a 0.1” (2.5 mm) load penetration with the dosage of 0.3gr acrylamide polymer / liter of water and 1.5% cement was the best, while with respect to the test of direct cut with the dosage of 0.3gr acrylamide polymer / liter of water and 0.5% cement was the best, finally, in the permeability test using the acrylamide polymer additive and cement make it more impermeable to the material.